The Influence of Suandei Fall on Art of Carving Artists in Woinap Village, Yapen Island District - Frans Falentinus Marahole; Amost Marahole; Roy Marthen Rahanra (Britain International for Academic Research (BIAR-Publisher), 2021)
The art of carving, known as carving, or decoration with various flora, fauna, figurative and even geometric motifs which is an ornate image with some parts being concave and some parts convex both horizontally and vertically and elliptically arranged in a very beautiful image. (Study of Cultural Anthropology)(1) The carvings, which are known in the works of Decorative Arts, still survive and are in demand and are found in various areas such as the Biak Numfor Islands, Yapen Islands, Waropen Wondama Bay and various other areas that are included in the Kuripasai cultural family, Mananarmakeri, and Sairei. A special highlight in this writing is the carving motifs that are still practiced by carving craftsmen in Woinap Village, Wonawa District, Yapen Islands Regency, where until now there are very few carvers. This carving motif was inspired by the legend of